Aktuele kunst in België; 24/3 - 29/4/1979; inzicht/overzicht - overzicht/inzicht. - MUSEUM VAN HEDENDAAGSE KUNST GENT (Gent : Museum van Hedendaagse Kunst, 1979)
Bigot, Gary ; Charlier, Jacques ; Copers, Leo ; Cuvelier, Werner ; De Smet, Yves ; De Waele, Daniel ; Dujourie, Lili ; Geys, Jef ; Leisgen, Barbara & Michael ; Lohaus, Bernd ; Matthys, Danny ; Mesmaeker, Jacqueline ; Panamarenko ; Queeckers, Bernard ; Rombouts, Guy ; Somerlinck, Jef ; Van Snick, Philippe ; Vercruysse, Jan ; Wéry, Marthe
kunstcatalogus